(untitled) (Revista Contexto & Educação, 2021)
Technological resources are increasingly present in people’s daily lives and in the most diverse situations, such as in science museums. In order to investigate whether the technology has been used in museums, academic production was analyzed from articles published in Qualis A1 magazines, in the teaching area, in the period from 2015 to 2019. 13 magazines were analyzed and 23 were identified articles based on the descriptors: museums, technology and technology in museums. Subsequently, these articles were grouped by categories in the light of content analysis. The results showed a decrease in publications about museums and a discreet, but not significant, increase in publications in the area of ​​technology. No publication was found regarding the use of technology in museums. Thus, the present study brings important developments in the sense of signaling the lack of work that investigates how technology has been incorporated into museums, since it is a current topic and of great social impact.